2003
DOI: 10.1017/s0033291703008183
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of brief cognitive behaviour therapy versus treatment as usual in recurrent deliberate self-harm: a decision-making approach

Abstract: Cost-effectiveness acceptability curves demonstrate that, based on the evidence currently available, to reject MACT on traditional grounds of statistical significance and to continue funding current practice has <10% chance of being the correct decision in terms of cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 27 publications
(24 reference statements)
0
64
0
1
Order By: Relevance
“…CEACs can now be found in major medical journals such as BMJ [1][2][3][4][5], New England Journal of Medicine [6,7], Lancet [8], Circulation [9], Chest [10] as well as health economics and health technology assessment journals [11][12][13][14][15][16][17]. Given the widespread dissemination of this technique it is important to ensure that both analysts and potential users of the information understand the nature and interpretation of these curves.…”
Section: Introductionmentioning
confidence: 99%
“…CEACs can now be found in major medical journals such as BMJ [1][2][3][4][5], New England Journal of Medicine [6,7], Lancet [8], Circulation [9], Chest [10] as well as health economics and health technology assessment journals [11][12][13][14][15][16][17]. Given the widespread dissemination of this technique it is important to ensure that both analysts and potential users of the information understand the nature and interpretation of these curves.…”
Section: Introductionmentioning
confidence: 99%
“…behaviour that have produced negative findings, 11,[13][14][15][16][17][18] although clearly another explanation is that the interventions were simply ineffective. A small number of trials have shown positive findings, but such trials are often dismissed as being of limited generalizability.…”
Section: Methodological Problems In Suicidologymentioning
confidence: 99%
“…In the absence of demonstrated cost-effectiveness data, some would argue that a reliance on cost-minimization analysis or inferences made from cost-effectiveness acceptability curves is an adequate basis for justifying use of public funds, particularly when the cost of services for self harm are so great. 17 Although the policy ideal is to implement only those policies that are cost-effective, social values are also important, particularly when the tools of economic analysis can be quite blunt. 36 …”
Section: Potential Solutionsmentioning
confidence: 99%
“…68 One other study has been reviewed. The study by Byford and colleagues 69 was an economic evaluation alongside a clinical trial of MACT that collected costs and outcome data, but it was concerned with self-harming patients. Although BPD patients were a subgroup in this study, full economic evaluation was not undertaken for this subgroup and so it should have been excluded from this review.…”
Section: Systematic Review Of Existing Economic Literature Searchmentioning
confidence: 99%
“…Cost-effectiveness of brief cognitive behaviour therapy versus treatment as usual in recurrent deliberate selfharm: a decision-making approach 69 The Byford study is a cost-effectiveness analysis of data from an RCT [Prevention of Parasuicide by Manual-Assisted Cognitive Behaviour Therapy (POPMACT)] comparing MACT with TAU for the treatment of people with recurrent episodes of DSH. The trial was conducted by Tyrer and colleagues, 58 in five centres in Glasgow, Edinburgh, Nottingham, West London and South London.…”
Section: Byford and Colleagues (2003)mentioning
confidence: 99%